Development of Healthy Beverages made from Germinated Parboiled Rice Blended with Juices from Local Fruits - Wanreungroun, Thitirut; Somrug, Krongjai; Kirdmalai, Nuntakan (Ratchaphruek Journal, 2020)
The purposes established for the study of developing healthy beverages made from germinated parboiled rice blended with juices from local fruits product included the following: 1) to develop healthy beverage recipes and to test the consumers’ acceptance of the developed beverages, and 2) to analyze and find out the physical values of the developed beverages. Four recipes were developed for making healthy beverages of germinated parboiled rice mixed with juices from local fruits. Main ingredients for Recipe ONE consisted of 105 aromatic jasmine rice (Hommali) and antidesma (Mao) juice; Recipe TWO comprised 105 aromatic jasmine rice and mulberry juice; for Recipe THREE were riceberry and antidesma juice; and Recipe FOUR were riceberry and mulberry juice. It was found that the healthy beverage made from the germinated parboiled riceberry and antidesma (Mao) juice provided better color, scent, and taste than other recipes (P<0.05). The physical tests of the developed recipes revealed these results: the drink from 105 germinated parboiled aromatic jasmine rice blended with the antidesma juice gave the highest L color; the drink from the germinated parboiled riceberry mixed with the antidesma juice bestowed the highest a color, the drink from the germinated parboiled riceberry blended with the mulberry juice yielded the highest b color (P<0.01). It was found that all four recipescontained the similar nutritious values and GABA.